Ecosystem-Based Restoration to Mitigate Eutrophication: A Case Study in a Shallow Lake - Konghao Zhu (Water, 2020)
Under the influence of human activities, eutrophication has become an increasingly serious global phenomenon, especially in shallow lakes. Many studies have shown that aquatic macrophytes play a significant role in controlling eutrophication, but only few of these studies are ecosystem based. In this paper, we applied a mass-balance ecosystem model to a shallow eutrophic lake (Lake Datong, China) as a case study with the aims of evaluating the status of ecosystem restoration via the recovery of aquatic vegetation and providing adaptive management suggestions. Results showed that the ecosystem was immature with weak energy flows and nutrient cycling largely due to the excessive submerged macrophytes and the lack of fish as consumer. In the early stages of restoration, the number of fish should be reduced, and aquatic vegetation needs to be recovered to mitigate eutrophication. When the aquatic vegetation community tends to be stable, herbivorous and omnivorous fish should be moderately stocked, and dead aquatic macrophytes should be harvested to maintain the healthy and sustainable development of the ecosystem. This study provided insights for the ecological restoration of shallow eutrophic lakes and revealed the urgent need for ecosystem-based restoration.